2015
DOI: 10.1177/2329496515604637
|View full text |Cite
|
Sign up to set email alerts
|

Do Irregularly Shaped School Attendance Zones Contribute to Racial Segregation or Integration?

Abstract: This research investigates if and how much the shapes of school attendance zones contribute to racial segregation in schools. We find that the typical school attendance zone is relatively compact and resembles a square-like shape. Compact zones typically draw children from local residential areas, and since local areas are often racially homogeneous, this suggests that high levels of racial segregation in the largest school districts are largely structured by existing residential segregation. Still, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 36 publications
1
45
1
1
Order By: Relevance
“…Prior literature (Saporito and Van Riper 2016) shows that attendance zones are about one standard deviation less irregularly-shaped than U.S. Congressional Districts. Since some Congressional Districts are notoriously irregular, this does not necessarily mean that the typical attendance zone in the typical school district is compact.…”
Section: Analysesmentioning
confidence: 89%
See 1 more Smart Citation
“…Prior literature (Saporito and Van Riper 2016) shows that attendance zones are about one standard deviation less irregularly-shaped than U.S. Congressional Districts. Since some Congressional Districts are notoriously irregular, this does not necessarily mean that the typical attendance zone in the typical school district is compact.…”
Section: Analysesmentioning
confidence: 89%
“…It is also possible that "gerrymandered" school attendance zones are associated with racial integration-a contention I make in this paper. The logic of this claim is straightforward: since people of the same race tend to cluster together in residential areas, irregularly-shaped zones that sprawl hither and yon have the potential to draw children from distant "black," "brown," and "white" residential areas (Saporito and Van Riper 2016).…”
Section: Introductionmentioning
confidence: 99%
“…GIS researchers have examined the shape of school districts in relation to internal and contiguous community demographics. Saporito (2017) and Saporito and Van Riper (2016) investigated the extent to which the shapes of school attendance zones were associated with racial segregation in schools. To make their determination, they tested the “irregularity” of school district shapes across the United States using GIS compactness measures .…”
Section: Overview Of Gis Analytic Techniquesmentioning
confidence: 99%
“…In their analysis of SABINS data, Saporito and Van Riper (2016) reported that most U.S. school districts are compactly shaped or square-like. Such shapes tend to mimic the racial homogeneity of the surrounding area, without much variation.…”
Section: Primary Research Themes In Gis Education Researchmentioning
confidence: 99%
“…Scholars who found that irregularly shaped boundaries alleviate racial and income segregation in schools make different assumptions about what an ideal compact shape looks like and, as a result, what measure can best assess irregularity. For example, Saporito and Van Riper (2016) combined three measures of irregularity: concavity, the Polsby-Popper index, and the convex hull index. With concavity, the ideal compact shape is any perfectly convex shape, such as a circle, rectangle, or triangle (Chambers & Miller, 2010).…”
Section: Refining the Quantitative Geospatial Techniques Applied By Rmentioning
confidence: 99%